The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/5614939
|View full text |Cite
|
Sign up to set email alerts
|

Ubenimex Combined with Pemetrexed Upregulates SOCS1 to Inhibit Lung Adenocarcinoma Progression via the JAK2-STAT3 Signaling Pathway

Abstract: To study the effects of ubenimex (UBE) combined with pemetrexed (PEM) on lung adenocarcinoma cell behavior and its molecular mechanism, the tissue samples from lung adenocarcinoma patients who received PEM chemotherapy, those with PEM combined with UBE chemotherapy, and healthy volunteers were retrieved and analyzed. The expression levels of the suppressor of cytokine signaling 1 (SOCS1) in the human lung adenocarcinoma cancer cell lines A549 and PC-9 and tissues were detected by qRT-PCR. MTT assay was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Khan et al found that the deficiency of SOCS1 increases susceptibility to hepatocellular carcinoma (HCC), thereby reinforcing cell adaptation to oxidative stress and fostering tumor growth . Chen et al demonstrated that the combination of Ubenimex and Pemetrexed could inhibit the JAK2-STAT3 signaling pathway by upregulating SOCS1 expression, thus impeding the development of cancer cells . The SYVN1 gene encodes E3 ligase synovium protein 1 (SYVN1), which involves the development and metastasis of hepatocellular carcinoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan et al found that the deficiency of SOCS1 increases susceptibility to hepatocellular carcinoma (HCC), thereby reinforcing cell adaptation to oxidative stress and fostering tumor growth . Chen et al demonstrated that the combination of Ubenimex and Pemetrexed could inhibit the JAK2-STAT3 signaling pathway by upregulating SOCS1 expression, thus impeding the development of cancer cells . The SYVN1 gene encodes E3 ligase synovium protein 1 (SYVN1), which involves the development and metastasis of hepatocellular carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…54 Chen et al demonstrated that the combination of Ubenimex and Pemetrexed could inhibit the JAK2-STAT3 signaling pathway by upregulating SOCS1 expression, thus impeding the development of cancer cells. 55 The SYVN1 gene encodes E3 ligase synovium protein 1 (SYVN1), which involves the development and metastasis of hepatocellular carcinoma. After knocking down SYVN1, the migration and invasion ability of liver cancer cells were decreased.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%